On Double-Headed Relative Clauses - Cinque, Guglielmo (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2017)
The present article documents the presence in a number of languages and language families (as well as in various child languages) of relative clauses displaying simultaneously an internal and an external head, and considers the implications of this finding for the general theory of relative clauses.